2014
DOI: 10.1038/ncomms6461
|View full text |Cite
|
Sign up to set email alerts
|

Giant enhancement in vertical conductivity of stacked CVD graphene sheets by self-assembled molecular layers

Abstract: Layer-by-layer-stacked chemical vapour deposition (CVD) graphene films find applications as transparent and conductive electrodes in solar cells, organic light-emitting diodes and touch panels. Common to lamellar-type systems with anisotropic electron delocalization, the planeto-plane (vertical) conductivity in such systems is several orders lower than its in-plane conductivity. The poor electronic coupling between the planes is due to the presence of transfer process organic residues and trapped air pocket in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 42 publications
9
70
0
Order By: Relevance
“…The shift in the positive direction by PBASE was explained by its p-doping effect through the charge transfer between the pyrene group and graphene44, which was also confirmed here by ultraviolet photoelectron spectroscopy, as the work function is increased by ∼0.3 eV (Supplementary Fig. 6).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The shift in the positive direction by PBASE was explained by its p-doping effect through the charge transfer between the pyrene group and graphene44, which was also confirmed here by ultraviolet photoelectron spectroscopy, as the work function is increased by ∼0.3 eV (Supplementary Fig. 6).…”
Section: Resultssupporting
confidence: 75%
“…Here, the high specificity of the sensor for DNA detection can mainly be attributed to the probe-DNA-specific recognition of its complementary partner. In addition, the use of PBASE linkers further reduces nonspecific electrostatic stacking binding of unrelated DNA on the graphene surface4446.…”
Section: Discussionmentioning
confidence: 99%
“…After PBASE was applied to the graphene surface, the statistical data of the 2D peak position were shifted to a higher frequency (∼3.27 cm −1 ), indicating p-doping by the π−π interaction between PBASE and graphene ( Figure 2C). 23,24 The mapping images also show that the average I 2D /I G ratio of PBASE-treated graphene (I 2D /I G = ∼1.87) is significantly lower than that of pristine graphene (I 2D /I G = ∼3.61) due to existence of some disorder on the graphene ( Figure 2D,E). The XPS survey data show the principal C 1s, O 1s, and N 1s core levels ( Figure 2F).…”
Section: Acs Nano Wwwacsnanoorg Articlementioning
confidence: 94%
“…[40] To further demonstrate the elemental composition of Fe-Ni hydroxide/GMC, C1s, Fe 2p, and Ni 2p X-ray photoelectron spectroscopy (XPS) spectraw ere investigated, and the results are shown in Figure4a-c. [41] The Fe 2p 3/2 peak in Figure 4b was greater than Fe 2p 1/2 because of spin-orbit coupling, and the ratio of Fe 2p 3/2 to Fe 2p 1/2 was approximately 2:1. [41] The Fe 2p 3/2 peak in Figure 4b was greater than Fe 2p 1/2 because of spin-orbit coupling, and the ratio of Fe 2p 3/2 to Fe 2p 1/2 was approximately 2:1.…”
Section: Resultsmentioning
confidence: 92%
“…The C1ss pectra revealed that the bindings tates of carbon were ÀSiÀC( 283.5 eV), ÀCÀCÀ (sp 2 , 282.6 eV), ÀC=CÀ (285.5 eV), ÀCÀO( 286.2 eV), ÀC=O( 287.2 eV) and O=CÀOÀ (289.0 eV). [41] The Fe 2p 3/2 peak in Figure 4b was greater than Fe 2p 1/2 because of spin-orbit coupling, and the ratio of Fe 2p 3/2 to Fe 2p 1/2 was approximately 2:1. The separation between the envelope (711.7 eV) and the satellite (719.2 eV) of Fe 2p 3/2 was7 .5 eV,w hichi sc onsistent with the Fe 3 + oxidation state and is different from the value for Fe 2 + ( % 5eV), [42,43] confirming that Fe existed as the Fe 3 + valence state in the Fe-Ni hydroxide/GMC.…”
Section: Synthesis and Characterization Of Fe-nih Ydroxide/gmcmentioning
confidence: 92%